The Effect of Cr Substitution on the Electronic Structure of CuAl1-xCrxO2 - WATSON, GRAEME WILLIAM; MORGAN, BEN; SCANLON, DAVID (APS, 2009)
The geometries and electronic structures of CuAl1?xCrxO2 have been investigated using density-functional theory with on-site corrections for strongly correlated systems (GGA+U) for x=0,(1/2),1. Al is found to be well described within the ionic model, with a valence charge corresponding to a +3 oxidation state. Substituting Cr for Al is predicted to increase the density of states at the top of the valence band, in agreement with experimental x-ray photoemission spectroscopy data. Analysis of atom-projected densities of states and valence charges suggests that this is due to increased covalency between Cr and O; the valence charge for O in the Cu-O-(Al,Cr) subunits changes from ?1.74 to ~?1.25 when Cr replaces Al. This produces an indirect oxygen-mediated change to the Cu d states.
PUBLISHED
Keywords: aluminium compounds; chromium; copper compounds; density functional theory; doping; electronic density of states; oxidation; strongly correlated electron systems; valence bands; X-ray photoelectron spectra